Evolution of randomized, controlled studies of medical therapy in chronic thromboembolic pulmonary hypertension. (1st May 2021) - Kim, Nick H.; Papamatheakis, Demosthenes G.; Fernandes, Timothy M.
Abstract : Although pulmonary endarterectomy (PEA) is the treatment of choice for chronic thromboembolic pulmonary hypertension (CTEPH), many patients have inoperable disease, and some have persistent or recurrent pulmonary hypertension (PH) after surgery. Alternative options (balloon pulmonary angioplasty (BPA) and PH‐targeted medical therapy) are, therefore, required. Studies of medical therapies for CTEPH have evolved since Aerosolized Iloprost Randomized (AIR), the first randomized, controlled study of a PH‐targeted therapy (inhaled iloprost) to include patients with CTEPH. Key learnings from these studies include the need to evaluate CTEPH separately from other types of PH, the importance of prospective operability adjudication as part of the protocol, and the need for sufficient duration to allow treatment benefits to become apparent. The 16‐week Chronic Thromboembolic Pulmonary Hypertension Soluble Guanylate Cyclase‐Stimulator Study 1 (CHEST‐1) study was the first to operationalize these learnings, demonstrating a significant mean improvement in 6‐minute walk distance (+46 m) and improvements in hemodynamic endpoints with riociguat versus placebo. Findings from previous studies will inform the design of future studies to address key issues related to combination medical therapy. Data on combinations of macitentan with phosphodiesterase type 5 inhibitors or oral prostanoids are available from MERIT, the first study to allow such regimens. No data on combinations including riociguat, the only licensed medical therapy for CTEPH, are available. Studies are also needed for multimodality treatment, including medical therapy plus BPA, and medical therapy as a bridge to PEA in selected operable patients. To address these issues and improve patient outcomes, it is vital that we learn from current studies to improve future trial design.